Determinants of agricultural credit accessibility: A case study of sugarcane (Saccharum officinarum) farmers in Muzaffarnagar district - SINGH, GARIMA; SHASTRI, SWATI (The Indian Journal of Agricultural Sciences, 2025)
Access to credit is an important aspect that determines agriculture productivity and financial ability of the farmers. The study was carried out during October 2023 to November 2024 to analyse the factors that influence sugarcane (Saccharum officinarum) farmers’ access to credit in Muzaffarnagar district, Uttar Pradesh, India. For this study data were collected from 390 farmers through a semi-structured questionnaire and to analyse the data, a logistic regression model has been employed. The study examined the socio-economic, demographic, and geographical factors affecting credit accessibility among sugarcane farmers. The results showed that education, annual income, landholding and collateral availability all have a significant effect on credit accessibility. Our results draw attention to the importance of improving financial awareness, enhancing adequate collateral, and reducing institutional barriers in order to expand credit accessibility. The study provides important insights for government interventions aimed at strengthening the financial security of sugarcane producers and promoting sustainable agriculture in the region.